PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY YANG TERDAPAT PADA PERBANKAN SYARIAH DALAM PRESPEKTIF SHARIAH ENTERPRISE THEORY STUDI KASUS PADA BANK BRI SYARIAH DAN BANK MANDIRI SYARIAH - DEVI KUSNASARI, SINTIA (Jurnal Akuntansi AKUNESA, 2014)
This study are to describe and to analyze the social responsibility on islamic bank that  is  BRI  Syariah  and  Bank  Mandiri  Syariah Surabaya.  This  study  used  a qualitative  descriptive  method  with  case  study  approach of  annual  reports  and then  analysis  based  on  the  disclosure  of  social  responsibility  based  on  sharia enterprise  theory.  The  social  responsibility  of  BRI  Syariah  and  Bank  Mandiri Syariah Surabaya is reported in the Annual Report which is presented narratively and qualitatively. These result show that implementation the social responsibility of BRI Syariah and Bank Mandiri Syariah is same with conventional one.Keyword: CSR, sharia enterprise theory, Islamic Bank